PENERAPAN KOMUNIKASI BISNIS ISLAM PADA USAHA MIKRO KECIL DAN MENENGAH - Fahmi Priyayi Pinandita; Muhamad Tanzi Maulana (Gunung Djati Conference Series, 2025)
The application of Islamic business communication principles in the activities of Micro, Small, and Medium Enterprises (MSMEs) is an important basis in building businesses that are not only economically profitable, but also fair, ethical, and full of blessings. Values such as honesty, fairness, transparency, and social responsibility become the framework in building healthy and sustainable business interactions. This research relies on a literature study approach to examine how Islamic business communication principles are applied to MSMEs in Indonesia. The results show that these values are able to increase consumer trust, strengthen relationships between business actors, and encourage positive business growth. However, some obstacles are still faced, especially the lack of understanding of Islamic principles and not optimal adaptation to digital technology. Therefore, there is a need for continuous education and support in consistently applying Islamic values in MSME activities.